2014
DOI: 10.1186/1472-6882-14-342
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vitro and in vivo Biological Activities of Cheilanthes albomarginata Clarke

Abstract: BackgroundThe Cheilanthes albomarginata Clarke (CA), a fern belonging to Pteridaceae family, is found mainly in India, Nepal, Pakistan and Bhutan at an altitude of 1300–2700 m. It grows mostly in the rock crevices on slopes. Juice from the rhizome of CA has been used to treat peptic ulcer. In this study, the biological activities (antioxidant, anti-inflammatory, anti-adipogenic and anti-obesity) of the extracts of CA were investigated. The total phenolic content of each extract was quantified. This is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Various fractions were isolated from the extract and ethyl acetate fraction showed the strongest in vitro antioxidant properties including phenolic content, DPPH radical scavenging, hydrogen peroxide scavenging, and nitrite scavenging activity. The in vitro anti-inflammatory and antiadipogenic properties were measured in inflammation stimulated cells and ethyl acetate fraction showed the significant anti-inflammatory and antiadipogenic activities [ 63 ].…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…Various fractions were isolated from the extract and ethyl acetate fraction showed the strongest in vitro antioxidant properties including phenolic content, DPPH radical scavenging, hydrogen peroxide scavenging, and nitrite scavenging activity. The in vitro anti-inflammatory and antiadipogenic properties were measured in inflammation stimulated cells and ethyl acetate fraction showed the significant anti-inflammatory and antiadipogenic activities [ 63 ].…”
Section: Role Of Antioxidants In Inflammationmentioning
confidence: 99%
“…Six flavonoid compounds (kumatakenin 5-Oβ-glucoside, kaempferol-7-methyl ether, rhamnocitrin 3-O-β-glucoside, and kaempferol 3-O-β-glucoside) were isolated and identified from the ethyl acetate-soluble fraction of this plant, which has shown anti-inflammatory and antiadipogenic activities. From the in vivo study in rats, the crude methanol extract and phenolic fraction showed plasma triglyceride-lowering activity, as well as a reduction of weight of adipose tissue in high-fat-diet-induced obese rats [53].…”
Section: Paris Polyphylla Sm Melanthiaceae 9160305mentioning
confidence: 96%
“…Reactive oxygen species at high levels can have a deleterious effects on living systems leading to damage of cell structures, including lipids, proteins, and DNA (Lamichhane et al, 2014).…”
Section: Antioxidant Studiesmentioning
confidence: 99%